Lebensphilosophie e filosofia dell’educazione - Gennari, Mario (Studi sulla Formazione/Open Journal of Education, 2025)
The article explores the relationship between Lebensphilosophie – the philosophy of life – and the philosophy of education. After tracing the historical-conceptual origins of Lebensphilosophie, the essay delves into its connection with the philology of life, including through the Nietzschean analysis of German culture and Bildung. Furthermore, it examines its link with the hermeneutics of life, highlighting the role of comprehension and interpretation in the construction of human knowledge. The article converges on the tension between humanism and nihilism, as well as on the urgency of a philosophy capable of restoring meaning and dignity to the human experience of formation, education and instruction.